PROFIL PENGETAHUAN PEKERJA SEKS KOMERSIAL (PSK) TENTANG HIV/AIDS DI DUKUH NGLEBOK KECAMATAN CEPU KABUPATEN BLORA - Zulaika, Chusnul Zulaika Zulai (Jurnal Ilmu dan Teknologi Kesehatan, 2010)
Disease of infection of HIV / AIDS represent the problem of biggest health. Amount of suffered of HIV /AIDS in Indonesia in the year 2006 is 165.000 - 250.000. while in Central Java in the early year 2007 tendingto increase there are 1070 patient of HIV / AIDS consist of 830 patient of HIVDAN 240 patient of AIDS. InBlora during three year partake - partake in District Of Casket Hamlet of Nglebok and in Blora in KampongJust known 17 one who is infection of HIV, altogether PSK which are positive infection of HIV. So that can beformulated by problem " How level knowledge of PSK HIV about / AIDS in Hamlet of Nglebok Sub-District OfTambakromo District Cepu Sub-Province of Blora?".This Research aim to wish to know knowledge level at PSK about HIV / AIDS in Hamlet of NglebokDistrict Cepu Sub-Province of Blora in the year 2008.This Research type is descriptive and total used population of sample counted 50 people. Procedureintake of data with primary data and of secondary. Research Instrument the used is questioners.PSK knowledgeable of goodness that is 56 %. Where knowledge represent very important domain toforming of someone action. Education of majority responder is finish of SD counted 38 people (76). Majorityold age responder reside in at age 20 - 35 year counted 26 people (52).From this research can be concluded by knowledgeable majority of goodness 56%knowledgeable is36%, while less 8 %.Keyword : knowledge, PSK, HIV / AIDS